Internacionalização acadêmica no Brasil: estudo de políticas e estratégias nacionais e internacionais - Reis, Ana Carolina Ale dos (Universidade Federal de São Carlos, 2023)
The internationalization strategy of colleges and universities is a mobility phenomenon that has been gaining strength, even after the pandemic, not only for strengthening the image of countries - soft power - but also for attracting financial and human resources to these destinations. By providing several benefits of a professional and personal development nature, the experience of carrying out an exchange, especially the short-term ones - study tour, has become increasingly common among Brazilian students. Based on a bibliographical survey and interviews with people who are directly related to the study tour theme, this work analyzes and discusses the main characteristics that involve the short-term international school exchange process, in Brazil and abroad, and their intersections with tourism. It is expected that this study can stimulate discussions that contribute to the development of the internationalization of higher education in Brazil, as well as highlight the importance of publicizing the country as a study tour destination for foreign students.
Academic internationalization in Brazil: study of national and international policies and strategies
Internacionalización académica en Brasil: estudio de políticas y estrategias nacionales e internacionales
Keywords: Turismo de Intercâmbio; Study Tour; Internacionalização do Ensino Superior; Mobilidade Acadêmica; Educação Global; Exchange Tourism; Internationalization of Higher Education; Academic Mobility; Global Education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::TURISMO; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO